2022
DOI: 10.1029/2021wr031343
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Change‐Induced Transients in a Water Distribution Network: Laboratory Tests in a Looped System

Abstract: In pipe networks, the pressure plays a key role and, in particular, pressure variations due to transients can induce additional stresses not only on pipes, but also on the other components, such as junctions and devices.Traditionally, in transmission mains attention is focused on the effects of a valve maneuver, carried out to set an appropriate discharge, or pump trip that can give rise to severe overpressures (Liou & Wylie, 2016;Meniconi et al., 2018;. Very different is the approach with respect to transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Some studies have shown that the response of the WDN to these forcing factors depends on its characteristics and, in particular, on the topological structure (i.e., network connectivity) (Meniconi et al., 2022a, 2022b) as well as the presence of elements such as dead ends (Meniconi et al., 2018, 2021) and on diameter and material of pipes (Ellis, 2008; Karney & McInnis, 1990; Starczewska et al., 2014). Thus, each WDN is characterized by a different transient response in the face of a forcing factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that the response of the WDN to these forcing factors depends on its characteristics and, in particular, on the topological structure (i.e., network connectivity) (Meniconi et al., 2022a, 2022b) as well as the presence of elements such as dead ends (Meniconi et al., 2018, 2021) and on diameter and material of pipes (Ellis, 2008; Karney & McInnis, 1990; Starczewska et al., 2014). Thus, each WDN is characterized by a different transient response in the face of a forcing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been evidence that users' activity (Marsili et al, 2021), that is, the opening and closing of domestic devices, can also result in the generation of pressure waves of small entity but occurring almost continuously over the day, producing deterioration that tends to worsen over time and increase failure rate (Rezaei et al, 2015). Some studies have shown that the response of the WDN to these forcing factors depends on its characteristics and, in particular, on the topological structure (i.e., network connectivity) (Meniconi et al, 2022a(Meniconi et al, , 2022b as well as the presence of elements such as dead ends (Meniconi et al, 2018(Meniconi et al, , 2021 and on diameter and material of pipes (Ellis, 2008;Karney & McInnis, 1990;Starczewska et al, 2014). Thus, each WDN is characterized by a different transient response in the face of a forcing factor.…”
mentioning
confidence: 99%